The role of excess attractive particles in the elasticity of high internal phase Pickering emulsions. Issue 1 (29th November 2021) - Chae, Junsu; Choi, Siyoung Q.; Kim, KyuHan
Abstract : We investigate the role of excess colloidal particles in the continuous phase to explain the significantly greater elastic properties of high internal phase Pickering emulsions. Abstract : A high internal phase emulsion (HIPE), which has a volume fraction of dispersed phase of over 74%, shows a solid-like property because of concentrated polyhedral droplets. Although many studies have proposed theoretical and empirical models to explain the rheological properties of HIPEs, most of them are only limited to the emulsions stabilized by surfactants. In the case of high internal phase Pickering emulsions (HIPPEs), much greater values of elastic modulus have been reported, compared to those of surfactant-stabilized HIPEs, but so far, there have been no clear explanations for this. In this study, we investigate how colloidal particles attribute to the significantly high elasticity of HIPPEs, specifically considering two different contributions, namely, interfacial rheological properties and bulk rheological properties. Our results reveal that the flocculated structures of colloidal particles that possess a significant elasticity can be interconnected between dispersed droplets. Furthermore, this elastic structure is a crucial factor in the high elasticity of HIPPEs, which is also supported by a simple theoretical model.